PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN DI RUMAH HIJAB UMMU HAFIDZ KOTA GORONTALO - Sitti Nurfatimah Usman; Robiyati Podungge; Andi Yusniar Mendo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the effects of compensation and work motivation on turnover intention among employees at Rumah Hijab Ummu Hafidz in Gorontalo City. Compensation in this study includes direct compensation, such as salaries and incentives, and indirect compensation, such as allowances and work facilities. Methods:  This study involved 50 respondents among employees at Rumah Hijab Ummu Hafidz, Gorontalo City. The research method is quantitative, using data collection techniques through questionnaires. The sample in this study comprises all active employees at Rumah Hijab Ummu Hafidz, using a census method. The data analysis tools used include classic assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²), using SPSS 27.Results: The research shows that, in part, the variables of compensation and work motivation have a positive and significant effect on turnover intention. Simultaneously, both have a considerable effect, accounting for 93.7% of turnover intention, while 6.3% is influenced by factors outside this research model, such as work environment conditions, psychological pressure, or family factors. Thus, improving fair compensation and creating good work motivation can reduce employees' intention to leave their jobs. Keywords: Compensation, Turnover Intention, Work Motivation